2017
DOI: 10.1080/14767058.2017.1368480
|View full text |Cite
|
Sign up to set email alerts
|

Maternal serum and fetal cord-blood ischemia-modified albumin concentrations in normal pregnancy and preeclampsia: a systematic review and meta-analysis

Abstract: This meta-analysis, the first of its kind showed that the increased serum IMA concentrations were indicative of increased oxidative stress in NP and PE. Measurement of maternal serum IMA and fetal cord-blood IMA concentrations were useful as simple, novel, and inexpensive markers of oxidative stress (OS) status in PE patients. Future large-scale studies are needed to explore IMA in relationship to the disease severity in PE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 40 publications
0
10
0
1
Order By: Relevance
“…A meta-analysis of publications available in NCBI PubMed and other databases conducted by Reddy et al [153] showed that IMA is a potentially useful biomarker for PE with reasonable accuracy (AUC = 0:860). The authors concluded that the evaluation of maternal serum IMA and fetal cord-blood IMA concentrations is useful as a simple, novel, and inexpensive marker of oxidative stress status in PE patients [154].…”
Section: Obstetrics and Gynecologymentioning
confidence: 99%
“…A meta-analysis of publications available in NCBI PubMed and other databases conducted by Reddy et al [153] showed that IMA is a potentially useful biomarker for PE with reasonable accuracy (AUC = 0:860). The authors concluded that the evaluation of maternal serum IMA and fetal cord-blood IMA concentrations is useful as a simple, novel, and inexpensive marker of oxidative stress status in PE patients [154].…”
Section: Obstetrics and Gynecologymentioning
confidence: 99%
“…Ischemia Modifi ed Albumin has been found to be very useful marker for the detection of acute myocardial ischemia but now it is being used to investigate the relation of many diseases to hypoxia/ ischemia such as preeclampsia, appendicitis, hepatitis B-related chronic liver diseases, intestinal ischemia necrotizing enterocolitis. 22,[24][25][26][27][28] Similarly, we used IMA to demonstrate hypoxia/ischemia in the etiopathogenesis of PD in our study. The secretory endometrium contains plenty amount of arachidonic acid, which is used for production of various prostaglandins and leukotrienes during menses.2 9 These prostaglandins and their metabolites are responsible for the symptomatology of PD such as pain, headache, nausea and vomiting, and backache.…”
Section: Discussionmentioning
confidence: 99%
“…However, in our study, the low diagnostic utility of measurements of the oxidative stress marker IMA in T21 pregnancy were demonstrated. Although IMA and AGE have never been measured in T21 pregnancy before, extensive data in the literature suggest their promising diagnostic utility in pre-eclampsia and pregnancy hypertension [57,58]. Despite confirmation of a higher level of oxidative stress, the IMA and AGE levels have been shown to not be remarkably increased in various complications related to T21 gestation [34,42,[59][60][61].…”
Section: Strength and Limitationsmentioning
confidence: 99%